HUBUNGAN POWER OTOT LENGAN DENGAN KEMAMPUAN TOLAK PELURU SISWA SMA YP IT MUTIARA KECAMATAN PINGGIR - Jumaini Jumaini; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study is whether there is a relationship with the arm muscle power repulsion results in a high school student shot put IT YP Mutiara District of Uptown. The method used is the correlation method is a method used to determine the level of correlation between the different variables. The population in this study were high school students YP IT Mutiara District of Uptown, which amounts to 25 people. The sample selection using total sampling technique thus the sample in this study are the male and female of high school students YP IT Mutiara District of Uptown ie 25 people. Analysis of data using correlation and regression analysis. Before testing the hypothesis to test hypotheses and analysis requirements for linearity test regression line by F test using significance level of 5%. Obtained Fhitung = 27.37> F table = 4:24, and the regression equation is Y = 3.47 + 0.26X. Furthermore, to examine the mean correlation between variables X and Y then tested the significance of significance by using the formula t test. From the results of the calculation are known tcount = 5.23, while table = 1,714. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "the presence of a significant correlation between muscle power arm with repulsion results in a high school shot-put style orthodox Uptown District of YP IT Mutiaras" is received, the count r value of 0.737.Keywords : arm and shoulder muscles power, Shot Put